Turning Sorrow into Song: Silence, Absence and Unreadability in Elizabeth Rosner’s Gravity - Laura Miñano Mañero (European Journal of American Studies)
This article explores Elizabeth Rosner’s second-generation poetic rendition of the Holocaust, Gravity (2014), offering an insightful framework to further scholarship on the intergenerational transmission of trauma, examined through the lens of postmemorial poetry. I specifically concentrate on Rosner’s poetry of remembrance as it dwells on the role of language and silence in representing the vicarious experience of the Shoah. Through a sustained exploration of the traces of an inherited trauma that renders the past inaccessible, simultaneously present and occluded, the poet endows the motif of silence with unique meaning. Surrendering to the compulsions of verse, attempting to restore to language what is lost, without ever succeeding, and integrating the legacy of the Old into the New World, I contend that Rosner reaches a form of posttraumatic growth that is only made possible through poetic engagement.